Genetic Diversity of Porang (Amorphophallus muelleri Blume) in Malang, East Java based on Morphology and Molecular Markers (ITS2, trnL, and matK): Genetic Diversity of Amorphophallus muelleri Blume in Malang - Nensy Marantika, Riza; Arumingtyas, Estri Laras; Azrianingsih , Rodiyati (Journal of Tropical Life Science, 2025)
Porang (Amorphophallus muelleri) is an herbaceous plant belonging to the Araceae family that is distributed in Java, including the Malang region. This study aimed to determine the morphological and genetic variation of porang in the Malang region based on ITS2, trnL, and matK molecular markers. Porang samples were collected from seven populations in Malang district, i.e., Kasembon, Ngantang, Pujon, Dampit, Kalipare, Pagak, and Bantur. Observa-tions of porang included 27 morphological traits, and young leaves were ob-tained for DNA extraction. Then, ITS2, trnL, and matK were amplified using a specific primer pair. Morphological traits exhibited similarity in color, surface, shape, and petiole pattern, while differences were apparent in morphological size parameters. Porang petiole of all the populations in Malang is green with a white prismatic pattern and linear lines. The 438 bp ITS2 sequences con-tained 390 bp invariable sites and 48 bp variable sites, whereas the 555 bp trnL intron sequences consisted of 511 bp invariable sites and 44 bp variable sites, and the 738 bp matK sequences comprised 713 bp invariable sites and 25 bp variable sites. The ITS2 sequences of the seven porang populations had the highest number of variable sites compared with the trnL and matK sequences. The total number of haplotypes based on ITS2, trnL, and matK was 11, with a haplotype diversity value of 1.00. Haplotype 1–7 were A. muelleri, haplotype 8 was A. paeoniifolius, and haplotypes 9, 10, and 11 were A. bulbifer, A. konjac, and A. sumawongii, respectively (from Genbank). Fur-thermore, phylogenetic analysis using Maximum Likelihood, Neighbor Joining, and Maximum Parsimony based on the ITS2, trnL, and matK sequences showed consistent clades. Clade 1 comprises A. muelleri, which is divided into 3 subclades. Subclade 1 comprises Kasembon, Ngantang, Pagak, Dampit, subclade 2 comprises Kalipare and Pujon, and subclade 3 is Bantur. Clade 2 is A. bulbifer, and clade 3 consists of outgroups.